Ethnobotanical Study of Medicinal Plants among Lao, Tai, and Khmu Ethnic Groups in Pakkading District, Bolikhamxai Province, Laos - Souladeth, Phetlasy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research investigated the ethnobotanical knowledge of medicinal plant use among three ethnic groups (Lao, Tai, and Khmu) in Pakkading District, Bolikhamxai Province, central Laos. A total of 111 medicinal plant species were documented, representing 97 genera and 55 families. Quantitative analysis was conducted using Use Value (UV) and Informant Agreement Ratio (IAR). Cluster analysis based on Jaccard’s Similarity Index (JI) was applied to assess the similarity of medicinal plant use among the three groups. The most important species were Curcuma longa L. (UV = 1) for the Lao; Chromolaena odorata (L.) R. M. King & H. Rob. and Curcuma longa (UV = 0.98) for the Tai; and Phyllanthus emblica L. (UV = 0.95) for the Khmu. According to the IAR, all three groups showed high consensus values, particularly the Lao, indicating strong agreement on the use of plants for specific ailments. These findings suggest that certain species are widely recognized and consistently used for traditional treatments. Comparison of medicinal plant use showed the highest similarity between the Lao and Tai, as reflected in a high Jaccard Index, whereas the Khmu exhibited the greatest difference relative to the other two groups. The extensive documentation of medicinal plants and the identification of culturally and historically significant species highlight the importance of forest conservation for safeguarding both the livelihoods and ethnobotanical knowledge of local and indigenous communities in Bolikhamxai Province. This study examined the medicinal plant knowledge of the Lao, Tai, and Khmu ethnic groups in Pakkading District, Bolikhamxai Province, central Laos. A total of 111 species from 55 families were recorded. Quantitative analyses (UV, IAR, and JI) revealed that Curcuma longa, Chromolaena odorata, and Phyllanthus emblica were the most important species. All groups showed high agreement in plant use, with the Lao and Tai sharing the greatest similarity, while the Khmu differed more. The findings highlight the rich traditional knowledge and the importance of conserving forests to protect local culture and livelihoods.